AVANTAJELE ȘI BENEFICIILE ACHIZIȚIILOR PUBLICE SUSTENABILE (ÎN CONTEXT INTERNAȚIONAL) - Rusu, Elena (CEP USM, 2022)
This paper presents arguments regarding the security of implementation of the Sustainable Public Objectives at the international level. To carry out the study, it authorizes an applicable traditional research method: monographic method, document analysis, comparison, trend analysis, etc. The conclusions appear as a result of the analysis of international documents, guides and case studies and reflection in order to be able to give to public expenditures for public expenditures for the purchase of products, services, project care favoring sustainable use.
Keywords: Sustainable Development; Sustainable Public Procurement; Green Procurement